2017
DOI: 10.1111/eva.12532
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of symbiont‐mediated resistance compromises biological control of aphids by parasitoids

Abstract: There is growing interest in biological control as a sustainable and environmentally friendly way to control pest insects. Aphids are among the most detrimental agricultural pests worldwide, and parasitoid wasps are frequently employed for their control. The use of asexual parasitoids may improve the effectiveness of biological control because only females kill hosts and because asexual populations have a higher growth rate than sexuals. However, asexuals may have a reduced capacity to track evolutionary chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…B), the fittest genotypes still performed better on this host than the least fit genotypes. In summary, these findings suggest that plant resistance factors will favor the fittest R. padi genotypes, but symbiont‐infected individuals will be favored when parasitoids are abundant (Käch et al ., ), although these aphids might not achieve optimal performance on a poor quality host plant. While the consequences of symbiont‐conferred parasitoid resistance for aphid biocontrol are increasingly recognized (Vorburger, ), symbiont‐mediated fitness trade‐offs that interact with plant defensive traits have received relatively little attention until recently (e.g., Frago et al ., ; Karley et al ., ) and should be taken into account when deploying crop resistance and natural enemies for integrated management of crop pests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B), the fittest genotypes still performed better on this host than the least fit genotypes. In summary, these findings suggest that plant resistance factors will favor the fittest R. padi genotypes, but symbiont‐infected individuals will be favored when parasitoids are abundant (Käch et al ., ), although these aphids might not achieve optimal performance on a poor quality host plant. While the consequences of symbiont‐conferred parasitoid resistance for aphid biocontrol are increasingly recognized (Vorburger, ), symbiont‐mediated fitness trade‐offs that interact with plant defensive traits have received relatively little attention until recently (e.g., Frago et al ., ; Karley et al ., ) and should be taken into account when deploying crop resistance and natural enemies for integrated management of crop pests.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cowpea aphid, Aphis craccivora (Koch), is attacked by a number of Braconid wasps, including Binodoxys communis (Gahan), B. koreanus (Stary), L. orientalis (Stary & Rakhshani), and A. colemani; H. defensa infection did not protect aphids against L. orientalis or A. colemani, but did provide resistance to B. communis and B. koreanus (Asplen et al, 2014). The authors hypothesized that differential protection conferred by endosymbionts against particular parasitoid species might be linked to particular H. defensa-APSE combinations, and recent work provides evidence for specificity of symbiont defense in relation to APSE strain and aphid and parasitoid genotype (Dennis et al, 2017;Käch et al, 2018;Martinez et al, 2018). These factors could explain why H. defensa provided protection to R. padi against A. colemani (this study) and to Ap.…”
Section: The Outcome Of a Symbiont-aphid-parasitoid Relationship Is Smentioning
confidence: 99%
See 1 more Smart Citation
“…In the green peach aphid ( Myzus persicae ) or the black bean aphid ( Aphis fabae ), for example, clones harbouring defensive symbionts are much more resistant than the most‐resistant clones lacking these symbionts (von Burg et al ., ; Vorburger et al ., ). Laboratory experiments indeed confirmed that clones possessing heritable defensive symbionts are under strong positive selection in the presence of parasitoids (Herzog, Müller & Vorburger, ; Oliver et al ., ; Käch et al ., ).…”
Section: Defensive Symbionts Affect Key Determinants Of Host–parasitementioning
confidence: 97%
“…At least four species of facultative symbionts, namely Hamiltonella defensa, Serratia symbiotica, Regiella insecticola (Moran, Russell, Koga, & Fukatsu, 2005) and a symbiont referred to as X-type (Guay, Boudreault, Michaud, & Cloutier, 2009), include strains that increase aphid resistance to parasitoid wasps (Heyworth & Ferrari, 2015;Oliver, Russell, Moran, & Hunter, 2003;Vorburger, Gehrer, & Rodriguez, 2010). Parasitoids are important natural enemies of aphids (Schmidt et al, 2003), hence the possession of resistance-conferring symbionts can be under strong positive selection (Herzog et al, 2007;Käch, Mathé-Hubert, Dennis, & Vorburger, 2018;Oliver et al, 2008). However, this selective advantage may be lost or even reversed in the absence of parasitoids, because the possession of defensive symbionts can also entail costs to the host.…”
Section: Introductionmentioning
confidence: 99%